How to steal a dragon's sword : the heroic misadventures of Hiccup the Viking - Cowell, Cressida (Cowell, Cressida. How to train your dragon ;, 2012)
"A dragon rebellion is coming-filled with the meanest, nastiest dragons in the Archipelago. Razor-wings, Tongue twisters, and Vampire Ghoul deaths are attaching Vikings and seem to be seeking one soul in particular: Hiccup Horrendous Haddock the Third! Only a King can save them...and only a champion with all of the King's Lost Things can be King. In his adventures, Hiccup has collected quite a few "things" himself. But can a scrawny Viking save the entire Archipelago from certain doom? To find out, Hiccup will have to outwit a witch, fight his arch-enemy, and beat back an army of bloodthirsty dragons with just one sword."--P. [4] of cover.